2010
DOI: 10.1089/adt.2010.0313
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Synergistic Combinations of F508del Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) Modulators

Abstract: Cystic fibrosis (CF) is an inherited, life-threatening disease caused by mutations in the gene encoding cystic fibrosis transmembrane conductance regulator (CFTR), an ABC transporter-class protein and ion channel that transports ions across epithelial cell membranes. The most common mutation leads to the deletion of a single phenylalanine, and the resulting protein, F508del-CFTR, shows reduced trafficking to the membrane and defective channel gating. The ideal therapeutic approach would address both of these d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 57 publications
(69 reference statements)
2
14
0
Order By: Relevance
“…It remains to be determined whether the limited efficacy of available correctors can be overcome with improved understanding of the folding pathway and molecular partners of F508del-CFTR. As a more immediate approach to enhance efficacy, it has been shown that combinations of F508del correctors can have additive or even synergistic effects (Bridges 2010; Lin et al 2010), supporting the idea that more than one cellular mechanism is relevant to the cellular recognition and degradation of F508del-CFTR. The use of CFTR potentiators in combination with CFTR correctors represents another option to overcome deficits in efficient functional rescue for the protein.…”
Section: Correctorsmentioning
confidence: 95%
“…It remains to be determined whether the limited efficacy of available correctors can be overcome with improved understanding of the folding pathway and molecular partners of F508del-CFTR. As a more immediate approach to enhance efficacy, it has been shown that combinations of F508del correctors can have additive or even synergistic effects (Bridges 2010; Lin et al 2010), supporting the idea that more than one cellular mechanism is relevant to the cellular recognition and degradation of F508del-CFTR. The use of CFTR potentiators in combination with CFTR correctors represents another option to overcome deficits in efficient functional rescue for the protein.…”
Section: Correctorsmentioning
confidence: 95%
“…Hundreds of compounds classified as CFTR correctors have been identified in literature to date (Pedemonte et al, 2005; Van Goor et al, 2006; Carlile et al, 2007; Kalid et al, 2010; Lin et al, 2010; Van Goor et al, 2011). Most of these molecules are deemed unsuitable for clinical use namely due to low efficacy, cell type specificity, and/or toxicity profiles.…”
Section: Mechanism Of Action Of Existing Corrector Compoundsmentioning
confidence: 99%
“…It is interesting to note that previous corrector screens have used chemical libraries of 2,000–164,000 compounds, and typically the hit rate is ∼0.01–0.03% (Lin et al, 2010). This low yield suggests that larger libraries would be more successful.…”
Section: Drug Discoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Even after corrector treatment, F508del-CFTR has <15% the activity of CFTR wild-type (WT), and the corrector efficacy may vary depending on the cell type examined (13)(14)(15)(16). More robust rescue can be achieved by using a combination of correctors, which enhances rescue to levels greater than individual compound actions (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%